Revealing Masculinity in BTS’s Music: Between Self Identity and Market Desire - Frizki Yulianti Nurnisya; Sofia Hasna (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
Previous studies assessed that the Korean Wave, including the music group Bangtan Sonyeondan (BTS), had campaigned for a different side of masculinity. BTS, through their music, seems to carry the concept of a